PENGARUH PEMBERIAN MINUMAN BERENERGI YANG MENGANDUNG ASPARTAM TERHADAP GAMBARAN HISTOPATOLOGI RENAL TIKUS JANTAN (Rattus norvegicus L.) - Cindy Mentari; Des suryani (ANATOMICA MEDICAL JOURNAL | AMJ, 2018)
ABSTRACTBackground: Energy drinks containing aspartame are commonly consumed by the public, the use of aspartame in energy drinks causes controversy regarding its safety against kidneys especially when consumed in excess. Objective: This study aimed to determine the effect of energy drinks containing aspartame on histopathology renal male rats (Rattus norvegicus L .) ". Method: Invivo experimental study on mice with posttest only with control group design. Rats were divided into 5 groups: negative control group (KN) which was only given aquades, positive control 1 (KP1) given ADI dose aspartame (50 mg / kg / day), positive control 2 (KP2) given toxic dose aspartame (75 mg / kgbb / day), treatment 1 (P1) given ADI dose of energy drinks aspartame (50 mg / kg / day), and treatment 2 (P2) given doses of aspartame doses of energy (75 mg / kg / day). and treated for 28 days. Renal histopathology was analyzed qualitatively. Glomerular and tubulus proximal degeneration degree data were analyzed using the Kruskal-walis test and Mann-Whitney post Hoc test. Results: Giving energy drinks containing aspartame caused glomerular and renal proximal tubular degeneration. There is a difference in the level of kidney damage between mice given ADI dose aspartame and mice given aspartame exceeding the ADI dose (p <0.05). There was no difference in the level of proximal tubular damage between mice given aspartame doses in excess of ADI with mice given energy drinks contains aspartame both at ADI doses and in doses exceeding the ADI level (p> 0.05). Conclusion: Energy drinks containing aspartame cause hydrophic degeneration in the glomerulus and proximal tubules of male rats. Other contents in energy drinks may aggravate the conditions of hydrophic degeneration in the glomerular and proximal tubular of  rat that are given energy drinks according to ADI doses, especially if given in doses that exceed ADI doses